2012
DOI: 10.1371/journal.pone.0038859
|View full text |Cite
|
Sign up to set email alerts
|

High Quality Long-Term CD4+ and CD8+ Effector Memory Populations Stimulated by DNA-LACK/MVA-LACK Regimen in Leishmania major BALB/c Model of Infection

Abstract: Heterologous vaccination based on priming with a plasmid DNA vector and boosting with an attenuated vaccinia virus MVA recombinant, with both vectors expressing the Leishmania infantum LACK antigen (DNA-LACK and MVA-LACK), has shown efficacy conferring protection in murine and canine models against cutaneus and visceral leishmaniasis, but the immune parameters of protection remain ill defined. Here we performed by flow cytometry an in depth analysis of the T cell populations induced in BALB/c mice during the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…Thus, suggesting that the changes observed in the proportion of T cell subsets are minimally affected by differences in cellularity. In addition, our results are in agreement with recent publications showing that CD8 + effector memory cells (Reyes-Sandoval et al, 2011; Rigato et al, 2011; Sánchez-Sampedro et al, 2012) and CD4 + effector memory cells (Sánchez-Sampedro et al, 2012) have a relevant role for long-term protective immunity against parasites in some vaccination approaches as these cells are able to mount a rapid response after encountering the antigen (Colpitts and Scott, 2010). Besides, despite the ethical difficulties of working with human spleen samples, we were able to determine that the number of T cells increased after exPv stimulation.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, suggesting that the changes observed in the proportion of T cell subsets are minimally affected by differences in cellularity. In addition, our results are in agreement with recent publications showing that CD8 + effector memory cells (Reyes-Sandoval et al, 2011; Rigato et al, 2011; Sánchez-Sampedro et al, 2012) and CD4 + effector memory cells (Sánchez-Sampedro et al, 2012) have a relevant role for long-term protective immunity against parasites in some vaccination approaches as these cells are able to mount a rapid response after encountering the antigen (Colpitts and Scott, 2010). Besides, despite the ethical difficulties of working with human spleen samples, we were able to determine that the number of T cells increased after exPv stimulation.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, in several experimental vaccine models CD8+ T cells contribute to immunity [26], [27], [28], [29], [30], [31]. In contrast, we found that depletion of CD8+ T cells in L. braziliensis infected mice decreases inflammation.…”
Section: Discussionmentioning
confidence: 52%
“…Jayakumar et al examined a prime-boost immunization with DNA-MVA encoding tryparedoxin peroxidase (TRYP) with TLR1/2 adjuvant and induced CD4 + /CD8 + /IFN-γ + T cell related protection in Balb/c mice against L. panamensis infection [42]. Same results were obtained by LACK DNA-MVA immunization reported by Sanchez-Sampedro [43]. Overally these results suggested that DNA vaccines as equivalents of low dose parasite or antigen administration are able to induce Th1 skewed immune responses against primary high dose parasite challenge.…”
Section: Discussionmentioning
confidence: 77%
“…Among possible vector combinations, Human Adenovirus [44], Modified Vaccinia Ankara [42,43] and Salmonella [45] have received significant attention. However antivector immunity is the main drawback linked with these vectors.…”
Section: Discussionmentioning
confidence: 99%